Os vitrais da Catedral de Vitória-ES e seus doadores nas décadas de 1930 e 1940 - Lima, Mônica Cardoso de (2009)
This dissertation focuses on the stained-glass windows of the Catedral de Vitória, commissioned and installed from 1930 to 1940 and donated by political and religious institutions and families with great relevance on that historical context. It is our pur